Microbiome-based personalized nutrition as a result of the 4.0 technological revolution: A mini literature review. (October 2022) - Yeşilyurt, Neslihan; Yılmaz, Birsen; Ağagündüz, Duygu; Capasso, Raffaele
Abstract: Recent studies have shown that the microbiota, which is rich in variety and amount of nutrients, lives in the intestines and is thought to act as an organ, plays a significant role in the pathogenesis of health and diseases, and its composition is personal. Tailoring the diet, one of the most effective factors in the modulation of microbiota, for the promotion of health, the treatment of obesity, diabetes mellitus, cardiovascular and gastrointestinal system diseases are accepted as a potential therapeutic approach. In addition to practical methods such as anthropometric measurements used in the routine evaluation of nutrition, evaluation of food consumption records, and physical activity, some technological methods have been developed recently after the technology 4.0 revolution, which analyzes the host-microbiome with various methods. Although these next-generation technologies are promising for the evaluation of data on the individual microbiome and dietary interactions and the development of recommendations in this direction, there are several problems in data processing and analysis. Considering the impact of diet-microbiota interaction on health and disease, microbiota-based personalized dietary recommendations are promising, but still, there seems to be some way to go. In this mini-review, the diet-microbiota relationship in a personalized diet approach was evaluated and the potential use or usability of diet planning based on this approach was discussed. Graphical Abstract: ga1 Highlights: After technology 4.0 revolution, novel methods that analyze the microbiome have been developed. Considering diet-microbiota interaction, microbiota-based personalized diets are promising. Machine learning methods have a critic role in terms of microbiome-based personalized nutrition.